2017
DOI: 10.5005/jp-journals-10006-1523
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Acceptance of Contraception in Postpartum Women in Our Tertiary Hospital in Central India

Abstract: Introduction Contraception is an important intervention to reduce unwanted pregnancy and promote healthy and better living among women. As the population continues to rise, there will be overcrowding, a limiting of resources, and the quality of life will decline. India, as the first country in the world, initiated the National Family Planning program in the year 1951 with the objective of “reducing the birth rate to the extent necessary to stabilize the population at a level consistent with requirement of nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
7
1
Order By: Relevance
“…The current study found a lower percentage of SARC or LARC methods, which is still questionable, in contrast to previous studies demonstrating higher awareness of family planning methods and improved women's educational level [5]. Many factors that have been identified in many earlier studies, including lack of awareness, misinformation or persistent fear of side effects, and insufficient provider training, are likely to contribute to this small share which has become a potential barrier to uptake [6][7][8][9]. There were differences in the mix of modern contraception methods by sociodemographic characteristics such as educational attainment, place of residence, religion, caste, and wealth status [5,10,11].…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The current study found a lower percentage of SARC or LARC methods, which is still questionable, in contrast to previous studies demonstrating higher awareness of family planning methods and improved women's educational level [5]. Many factors that have been identified in many earlier studies, including lack of awareness, misinformation or persistent fear of side effects, and insufficient provider training, are likely to contribute to this small share which has become a potential barrier to uptake [6][7][8][9]. There were differences in the mix of modern contraception methods by sociodemographic characteristics such as educational attainment, place of residence, religion, caste, and wealth status [5,10,11].…”
Section: Discussioncontrasting
confidence: 94%
“…Further, the level of contraception use reflects the societies' attitudes and behaviours towards women and women's autonomy in the community [3,4]. The prevalence of contraception use also reveals gender equality and the quality of public health programs [5][6][7]. As a result, studies on contraceptive use have depicted the effects of contraception on demographic transition and population development [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative in-depth interviews are conducted with a random sample of 20 women, or until saturation, at each of the multiple time points (6 weeks, 6 months, 12 months and 24 months). This sampling is intended to provide a diverse representative sample of women’s perspectives [ 23 ]. In addition to the women, 35 husbands and 20 service providers, or until saturation, whichever is lower, will be interviewed for additional perspectives and triangulation purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Although India has experienced a decline in total fertility rate from 3.2 in 2000 to 2.3 in 2016 [16], there are wide disparities across states, rural-urban population and socioeconomic status, and there is an ongoing need for FP. Studies in India show that several obstacles prevent women from using postpartum contraception including: a lack of awareness [18][19][20][21][22], lack of marital communication about it [23], cultural attitudes [24], poor access to facilities [21], and poor counselling and other skills among health providers [16,24,25]. Even when women are aware of PPFP, studies have found a gap between their awareness and their actual utilisation due to barriers related to cultural, religious, fertility desires, duration of marriage and ANC service utilisation factors [22,25].…”
Section: Introductionmentioning
confidence: 99%